Criminal Social Work To Overcome Overcapacity In Post-Pandemic Prisons - M. Musa; Elsi Elvina; Evi Yanti (Universitas Airlangga, 2023)
There are currently various problems with prisons, including the emergence of problems regarding Over Capacity in prisons. Especially in the era of the Covid-19 pandemic, where prisons in Indonesia are not comparable to limited capacity space. In the renewal of criminal law, in this case, the Draft Law on the Criminal Code (RUU-KUHP) has discussed various alternative crimes, one of which is the existence of social work crimes. Research on social work crimes to overcome overcapacity in Post Pandemic Prisons (Prisons) uses normative legal research methods. The legal material used is to use library studies (Library Research). The regulations regarding social work crimes have been implemented in several countries such as the Netherlands, Portugal and Denmark. Social work crimes are also known as short-term deprivation of liberty and as an alternative attempt to carry out certain crimes with a short time.